A Comparison Study of the Solid Phantom and Water Phantom Using 6 MV and 15 MV Photon Energies, Depending on the Depth (Bangladesh Journal of Nuclear Medicine, 2024)
Water is such an environmental element that is considered the best human body tissue equivalent. In the field of dosimetry studies, water is frequently used. This comparison study is conducted by a solid phantom and a water phantom with 6 MV and 15 MV photon energies, respectively. A cylindrical-type ionization chamber is used to collect charge when beams are on. The distance between the ray source and the surface of the phantom was fixed at 100 cm i.e. to SSD (Source to Surface Distance) of during the experiment. Chamber travels 1 cm to 20 cm in both phantoms and an electrometer is attached in the experimental set-up to measure the charge. The field size was 10x10 cm2. The relative deviation ratio of the solid phantom to the water phantom was calculated. In the result, the maximum deviation was 0.64%, while the minimum deviation was 0%, corresponding to the depths of 1 cm and 2.5 cm, respectively, for 6 MV and at 15 MV, maximum deviation and minimum deviation were 1.90% and 0.167% respectively, corresponding to the depths of 1.5 cm and 13 cm. Therefore, it can be said that the solid phantom can overcome the disadvantages of installation time required for the water phantom and problems while water level changing for depth measurement, simultaneously can used to measure the radiological dose precisely.Bangladesh J. Nuclear Med. 27(1): 34-38, 2024